Evaluating the income loss associated with the african swine fever outbreak in brgy. lower marber matanao davao del sur : an assessment - Estrera, Nelda; Macion, Miraflor V.; Ruelan, Charisse Joy D. (Digos City : UMDC, 2023)
The outbreak of African Swine Fever (ASF) inflicted severe economic impacts on hog raisers, resulting in substantial livestock mortality, diminished income, and even the closure of farms. This study aimed to understand the economic impacts of the African Swine Fever (ASF) outbreak in Brgy. Lower Marber, Matanao, Davao del Sur, with a focus on income loss among hog raisers and multifaceted challenges faced by the affected hog raisers. An In-depth Interview (IDI) involving 10 participants was conducted to elicit responses regarding the impact of the African Swine Fever Outbreak on local hog raisers. Additionally, a phenomenology model was used to interview affected farmers and business owners to learn about their experiences and perceptions of the outbreak, how they have been handling the loss of income, and the crisis management techniques they have been employing. The analysis identified three themes, Direct Economic Losses among pig farmers, the Critical role of Prevention, Control, and Regulatory Compliance during the ASF crisis, and Compensation Schemes for farmers with ASF Losses, that specify a comprehensive understanding of the multifaceted challenges faced by hog raisers in Brgy. Lower Marber during ASF.
Keywords: Accountancy. -- Undergraduate Thesis